The Adoption and Effect of Artificial Intelligence on Human Resources Management - Tyagi, Pallavi (Emerald Studies in Finance, Insurance, and Risk Management Series, 2023)
Emerald Studies In Finance, Insurance, And Risk Management 7Bexplores how AI and Automation enhance the basic functions of human resource management